2019
DOI: 10.28991/esj-2019-01197
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aqueous Suspensions of Zero-Valent Iron Nanoparticles (nZVI) from Plant Extracts: Experimental Study and Numerical Modeling

Abstract: Plant extracts were produced from Camellia sinesis (Green Tea) and Punica granatum (pomegranate), and the total concentration of polyphenols was measured in terms of equivalent concentration of Gallic acid by using the Folin-Ciocalteu method. Zero Valent Iron nanoparticles (nZVIs) were synthesized in a semi-batch reactor by mixing a pre-specified volume of plant extract or Gallic Acid solution with an aqueous solution of iron sulfate heptahydrate (FeSO4·7H2O). To monitor the kinetics of nZVI synthesis, the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Then, the transplanting quality parameters were calculated according to the formula. Vernier calipers were used to measure the depth of penetration d and distance of the insertion point l and the inclination angle ɑ was measured by an optical goniometer (Karavasilis and Tsakiroglou, 2019). Each set of data was measured three times and the average value was taken as the final measurement data.…”
Section: Analysis Of the Performance Test Results Of The Seedling Pic...mentioning
confidence: 99%
“…Then, the transplanting quality parameters were calculated according to the formula. Vernier calipers were used to measure the depth of penetration d and distance of the insertion point l and the inclination angle ɑ was measured by an optical goniometer (Karavasilis and Tsakiroglou, 2019). Each set of data was measured three times and the average value was taken as the final measurement data.…”
Section: Analysis Of the Performance Test Results Of The Seedling Pic...mentioning
confidence: 99%
“…It has been revealed that phenolic compounds can decrease Fe 3+ to Fe 0 and improve the stability of the synthesized G-NZVI. The peak at 1636 cm -1 identifies the C=O stretching vibration in aldehyde and ketones (Karavasilis et al 2019). The peak at 1430 cm -1 was derived from the C-C stretch in ring aromatics.…”
Section: Characterization Of G-nzvimentioning
confidence: 99%
“…Such 'greener' processes for obtaining various nanomaterials have been widely reported and are gathering attention in several nanotechnology-based applications [18]. As one of the green synthetic approaches, plant extracts were considered for the synthesis of nanoparticles through biosynthetic routes which involve primarily the extraction of polyphenols, which are natural polymers acting as reducing agents and stabilizers [19][20][21].…”
Section: Introductionmentioning
confidence: 99%